PENERAPAN MODEL CONCEPT ATTAINMENT DISERTAI TEKNIK CONCEPT MAPPING DALAM PEMBELAJARAN FISIKA DI MA - Imam Yahya; Trapsilo Prihandono; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2017)
The research focused on the assembling of Concept Attainment models with Concept Mapping technique is students’ physics achievement and students’ activity. The purposes of this research are (1) to examine the difference achievement of using Concept Attainment models with Concept Mapping technique than Conventional models on learning physics, (2) to describe students’ activity using Concept Attainment models with Concept Mapping technique model in learning physic. The type of this research is experiment by using post-test only control group design. Sample of the research are X MIA 1 as an experiment class and X MIPA 2 as an control class.The techniques of data collection are observation, test,documentation, interview and portofolio. The techniques of data analysis using descriptive analysis and Independent Sample T-Test by SPSS 16 version. The result of the research are (1) students’ physics achievement acquired of analytical results Independent-Sample T-test Sig. (2-tailed) of 0,038, (2)average value students’ science activity is 83,9%. The research can be concluded that (1) there are significant difference of achievement of using Concept Attainment models with Concept Mapping technique than Conventional models on learning physics, (2) the student activity is in good criteria.